# Integration by Reverse Chain Rule

By recalling the chain rule, the Integration Reverse Chain Rule comes from the usual chain rule of differentiation. This skill is to be used to integrate composite functions such as
$e^{x^2+5x}, \cos{(x^3+x)}, \log_{e}{(4x^2+2x)}$.
Let’s take a close look at the following example of applying the chain rule to differentiate and then reverse its order to obtain the result of its integration.
\begin{aligned} \displaystyle \frac{d}{dx} \sin{x^2} &= \sin{x^2} \times \frac{d}{dx} x^2 \\ &= \sin{x^2} \times 2x \\ &= 2x \sin{x^2} \\ 2x \sin{x^2} &= \frac{d}{dx} \sin{x^2} \\ \therefore \int{2x \sin{x^2}} dx &= \sin{x^2} +C \end{aligned}

### Integration Reverse Chain Rule for Exponential Functions

(a)    Differentiate $e^{3x^2+2x-1}$.

\begin{aligned} \displaystyle \frac{d}{dx} e^{3x^2+2x+1} &= e^{3x^2+2x-1} \times \frac{d}{dx} (3x^2+2x-1) \\ &= e^{3x^2+2x-1} \times (6x+2) \\ &= (6x+2)e^{3x^2+2x-1} \end{aligned}

(b)    Integrate $(3x+1)e^{3x^2+2x-1}$.

\begin{aligned} \displaystyle \require{AMSsymbols} \require{color} (6x+2)e^{3x^2+2x-1} &= \frac{d}{dx} e^{3x^2+2x-1} &\color{red} \text{from (a)} \\ \int{(6x+2)e^{3x^2+2x-1}} dx &= e^{3x^2+2x-1} \\ \therefore \int{(3x+1)e^{3x^2+2x-1}} dx &= \frac{1}{2} e^{3x^2+2x-1} +C \end{aligned}

### Integration Reverse Chain Rule for Trigonometric Functions

(a)    Differentiate $\cos{3x^3}$.

\begin{aligned} \displaystyle \frac{d}{dx} \cos{3x^3} &= -\sin{3x^3} \times \frac{d}{dx} (3x^3) \\ &= -\sin{3x^3} \times 9x^2 \\ &= -9x^2 \sin{3x^3} \end{aligned}

(b)    Integrate $x^2 \sin{3x^3}$.

\begin{aligned} \displaystyle \require{AMSsymbols} \require{color} -9x^2 \sin{3x^3} &= \frac{d}{dx} \cos{3x^3} &\color{red} \text{from (a)} \\ \int{-9x^2 \sin{3x^3}} dx &= \cos{3x^3} \\ \therefore \int{x^2 \sin{3x^3}} dx &= -\frac{1}{9} \cos{3x^3} + C \end{aligned}

### Integration Reverse Chain Rule for Logarithmic Functions

(a)    Differentiate $\log_{e} \sin{x}$.

\begin{aligned} \displaystyle \frac{d}{dx} \log_{e} \sin{x} &= \frac{1}{\sin{x}} \times \frac{d}{dx} \sin{x} \\ &= \frac{1}{\sin{x}} \times \cos{x} \\ &= \cot{x} \end{aligned}

(b)    Hence, integrate $\cot{x}$.

\begin{aligned} \displaystyle \require{AMSsymbols} \require{color} \cot{x} &= \frac{d}{dx} \log_{e} \sin{x} &\color{red} \text{from (a)} \\ \therefore \int{\cot{x}} dx &= \log_{e} \sin{x} +C \end{aligned}

Differentiate $\displaystyle \log_{e}{\cos{x^2}}$, hence find $\displaystyle \int{x \tan{x^2}} dx$.       Have Fun!
Feel free to let us know if you are unsure how to do this in case 🙂 ## Mastering Integration by Parts: The Ultimate Guide

Welcome to the ultimate guide on mastering integration by parts. If you’re a student of calculus, you’ve likely encountered integration problems that seem insurmountable. That’s…

## Logarithmic Equations

We can use the laws of logarithms to write equations in different forms. This can be particularly useful if an unknown appears as an index…

#### Responses

1. Your integral with 2x sin(x^2) should be -cos(x^2) + c.

Similarly, your integral with x^2 cos(3x^3) should be sin(3x^3)/9 + c

1. Good pick. Thank-you!